Developing mental health literacy and cultural competence in elite sport. Issue 4 (4th July 2021) - Gorczynski, Paul; Currie, Alan; Gibson, Kass; Gouttebarge, Vincent; Hainline, Brian; Castaldelli-Maia, João Mauricio; Mountjoy, Margo; Purcell, Rosemary; Reardon, Claudia L.; Rice, Simon; Swartz, Leslie
Abstract: Mental health symptoms and disorders amongst elite athletes have attracted a great deal of discussion recently. Current epidemiological evidence illustrates that mental health symptoms and disorders in elite athletes are prevalent and a concern for athletes, coaches, and sport organizations. Recently, seven consensus, expert, or position statements have been written on the topic of mental health in elite sport. A strategy suggested by each of the seven statements – aimed at preventing and treating mental health symptoms and disorders in elite athletes, both individually and systemically – is to employ education interventions, specifically those based on increasing mental health literacy. Mental health literacy has come to include concepts related to knowledge of effective self-management strategies, challenging mental disorder stigma, awareness and use of mental health first-aid to assist others, and the facilitation of help seeking behaviors. In elite sport, questions remain about how mental health literacy can address the unique needs of the individual athlete, but also factor in their culture and their environment to identify how to prevent and treat mental health symptoms and disorders. The purpose of this commentary is twofold: 1) to explore the evolving concept of mental health literacy within elite sport which addresses individuals, their culture, and their environment, and 2) to propose strategies for best practice and research in mental health literacy within elite sport relying on collaboration between sports psychiatry, sport psychology, and clinical psychology.   Lay summary : Expert statements on mental health in elite sport have suggested the use of educational strategies to address poor mental health in elite athletes. This commentary explores the concept of mental health literacy within elite sport which addresses individuals, their culture, and their environment, and proposes strategies for best practice. Implications for Practice: Mental health literacy interventions should be based on detailed knowledge of developmental, cultural, and social issues related to sport participation and systemic issues within sport settings and organizations. Mental health literacy interventions should be designed in a manner which takes due account of cultural issues and contexts, where sport organizational goals are considered while helping organizations recognize and address mental health symptoms and disorders and also create sport environments where individuals can thrive. Mental health literacy interventions should have measurable impact on both organizations and individuals.